Multi-criteria assessment of climate smartness in rice-based cropping systems - Kiran Kumar Mohapatra; Amaresh Kumar Nayak; Ranjan Kumar Patra; Rahul Tripathi; Chinmaya Kumar Swain; Prasannajit Mishra; Manoranjan Satapathy; Rasu Eeswaran; Saheed Garnaik (Farming System)
Rice is one of the major staple food grains in the world and because of its higher water requirement, rice production is heavily threatened by climate change and extremes. As global warming and climate variabilities increasingly affect most of the rice growing regions including India, it is vital to introduce alternative options to rice-rice monocropping. To address this issue, we developed a climate smart index (CSI) to evaluate the climate smartness of different cropping systems such as, rice-sunflower (R-S), rice-maize (R-M), rice-black gram (R-BG) and rice-green gram (R-GG) compared to a conventional rice-rice (R-R) system grown in the eastern coastal belt of India. Diversifying rice-based cropping systems with legumes and sunflower significantly enhanced system productivity and the partial factor productivity of nitrogen by 33–41% and 40–45%, respectively over the rice-rice cropping system. Further, these systems reduced the global warming potential (GWP) by 46.3–51% compared to the rice-rice system. The soil organic carbon content increased by about 5–7 % due to the adoption of pulse crops. The climate-smart index for rice-sunflower (R-S), rice-black gram (R-BG), rice-green gram (R-GG), and rice-maize (R-M) systems were found to be higher than the rice-rice (R-R) system by 26.5%, 18.7%, 18.7%, and 14.9% respectively, on average across seasons. Hence, incorporating legumes and oilseed crops during the dry/minor seasons of the year in rice-based cropping systems can be proposed as a climate-smart alternative. Further, we propose conducting large-scale assessments of these cropping systems using spatial data to deliver decision tools for regional planning and policy formulation in agriculture.